ALIH KODE PADA KOMUNIKASI TOKOH PUNAKAWAN WAYANG CENK-BLONK VIDEO SERI 26: PNS OH PNS - Putu Agita Hary Devianti; Made Susila Putra (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
This research describes code switching in the Communication of Punakawan figures in Wayang Cenk-Blonk Video Series 26: PNS OH PNS. The analysis focuses on the type of code switching and the background of the causes for the code switching. Methods and techniques in this study were divided into three phases. The stage of providing data used the observation method with the basic technique of tapping which was then followed by the listening proficient technique and the interview method. In the data analysis stage, the intralingual and extralingual equivalents were used with the link-appeal technique to equalize the main things. Presentation of the results of data analysis used informal methods assisted by deductive and inductive techniques. The theory used is sociolinguistic theory. Based on the results of the analysis, it was found that there were some code switchings which used in the communication of Wayang Cenk-Blonk Video Series 26: Pns Oh Pns. The results of the analysis shows that there was a phenomenon of inner code switching and the factor causing code switching are the speaker factor, the talking topic factor, and the distraction factor for self-prestige.Keywords: code switching, punakawan figures, Cenk Blonk Puppets